Interpersonal Classroom Model: Learning from diversity in group practice courses - Tyler, Tee R (Groupwork, 2017)
The Interpersonal Classroom Model (ICM) is a teaching approach designed for group practice courses. The ICM places development of interpersonal communication skills as the central focus of in-class time. Guided by Kolb’s experiential learning theory, this teaching approach posits that students can prepare to work with diverse client populations by first learning to communicate across lines of social identity difference existing within the classroom. This paper presents three examples of social identity dialogues students engaged in during ICM group practice courses. These examples include the topics of race, religion, and sexual orientation. This paper concludes with initial benefits of the ICM approach reported by professors and undergraduate students. Keywords: group work; interpersonal classroom model; race; religion; sexual orientation; groupwork